The Use of Visual Supports to Overcome The Learning Difficulties Faced by Autism Spectrum Disorder (ASD) Sufferers in Autism UM Laboratory School (A Case Study of Three ASD Students) - AGRIANI, TRISAKTI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Agriani,  Trisakti. 2013.  The Use of Visual Supports to Overcome The Learning Difficulties Faced by Autism Spectrum Disorder (ASD) Sufferers in Autism UM Laboratory School (A Case Study of Three ASD Students) Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies,Universitas Brawijaya. Supervisor:Fatimah; Co-supervisor: Didik Hartono  Keywords:  Autism Spectrum Disorder (ASD), Learning Difficulties,  Visual Supports.   According to the Centers for Disease Control Prevention in 2013, Autism Spectrum Disorder now affects 1 in every 110 children in the world and the number of people who affected to autism are increasing at the rate of 10 to 17 percent per year. All people with autism have difficulties with social interaction and behavior, but the extent and type of difficult may vary.  It is obvious that actually with the impairments which exist in autism children, it will affect their learning process also. Therefore, becoming aware of the warning signs of learning difficulties faced by autism children and getting autism children the necessary help early can become the key to an autism child’s future.The writer focuses on the learning  difficulties which are faced by Autistic students in case of retaining the information  from the teachers and also focuses on the visual supports which are used by the teachers in Autism UM Laboratory School. This study used qualitative approach. The subjects being investigated were three autism  students on fifth grade at Autism UM Laboratory School. The data were obtained from observation in the VA Class and in the participants’ house in order to know kinds of learning difficulties based on Attwood’s theory in 1998, In answering the second problems of the study,  the writer also interviewed parents and the teachers of autism students in order to know the visual supports that they used to overcome the learning difficulties based on Hodgdon and Quill theory  in 1995.    The result reveals that there are  learning difficulties faced by  the  autism students such as tendency to make irrelevant comments, difficulty in understanding complex language, poor concentration, poor in organizational skills, easily stressed due to inflexibility, and also having  difficulty in Mathematic. Meanwhile, the visual supports which are used  are  real objects, photographs, visual schedules, visual task analysis, and also visual to structure their environment. The writer suggests the school establish positive relationships between the parents  and  teachers  who  are believed  to improve parental involvement and increase parents’ comfort level in working with the school. For  the next researchers,  they can  compare the learning difficulties of Autism Spectrum Disorder (ASD) with other disorders  and correlate with the achievement of the students.